Large-scale casting old sand grading regeneration and performance closed-loop sand conditioning process
Patent Information
- Application Number
- CN202611444697.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-17
- Publication Date
- 2026-11-03
AI Technical Summary
In the production of large castings, the performance of recycled sand fluctuates due to the mixing of recycled sand in different states, which affects the stability and efficiency of the casting process.
By graded regeneration of old sand, it is divided into first old sand stream and second old sand stream, and then subjected to regeneration treatment of different intensities and sand temperature adjustment to form different regeneration states. Then, it is mixed with new sand to form a stable bonding system.
It reduces the differences between batches of mixed sand when a high proportion of old sand is reused, and keeps the usable time, tensile strength and permeability within a stable range, making it suitable for continuous reuse of large castings.
Smart Images

Figure CN123024845A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of foundry sand recycling technology, and in particular to a large-scale foundry sand graded regeneration and performance closed-loop sand adjustment process. Background Technology
[0002] Large castings require a large amount of sand for molding. Recycling and reusing old sand is an important way for foundry enterprises to reduce the consumption of new sand and the discharge of waste sand. Existing resin sand or self-hardening sand old sand treatment lines usually include processes such as sand removal, crushing, magnetic separation, regeneration, dust removal, sand temperature adjustment, and mixed sand reuse.
[0003] Reusing old sand is not simply a matter of cleaning it and mixing it with new sand. Mechanically recycled old sand often retains old resin films, paint residues, or fine powdery substances on its surface. Patent CN206936276U points out that the old resin film remaining on the surface of mechanically recycled sand can affect the direct bonding between the new resin and the silica sand surface, thus affecting the strength of the sand mold. Another paper, "Effect of reclaimed sand additions on mechanical properties and fracture behavior of furan no-bake resin sand," studied furan self-hardening resin sand and concluded that changes in the amount of recycled sand added affect the mechanical properties and fracture behavior of the resin sand. Its strength change is related to the formation of bonding bridges between sand particles. Recycled sand is not a completely stable inert aggregate; its surface state and addition ratio will participate in the subsequent bonding system process.
[0004] Sand temperature is also a key factor in self-hardening sand mixing. According to patent publication number CN107983909A, excessively high temperature of recycled sand will accelerate resin curing and shorten the usable time after mixing, while excessively low temperature will affect the mixing effect and core strength. Patent publication number CN102847879A also mentions that during the hardening process of self-hardening furan resin sand, an increase in sand temperature will accelerate the curing speed. Therefore, in production, it is often necessary to adjust the amount of curing agent added according to the sand temperature.
[0005] Existing technologies mainly treat recycled sand as a single reuse sand stream, or adjust new sand and recycled sand to the same sand temperature range before adding resin, curing agent, and other binding systems. However, when a high proportion of recycled sand is reused in large-scale casting, the recycled sand will form different surface regeneration states after being treated with different regeneration intensities. The recycled sand with lighter regeneration maintains the morphology of the sand particles well, but has a relatively large amount of residual film on the surface and responds more slowly to the binding material. The recycled sand with stronger regeneration removes more residual layer on the surface, but has a higher degree of surface activation, frictional heat accumulation, and adsorption capacity, and responds more quickly to the binding system. If the two types of recycled sand are still uniformly introduced into the same sand temperature window and mixed with new sand, binding material, and hardening material in a fixed proportion, it is easy to cause fluctuations in the usable time, early strength establishment, and sand mold permeability under the same sand mixing formula. Summary of the Invention
[0006] The technical problem to be solved by this invention is: how to stabilize the bonding system after mixing sand and reduce the performance fluctuation between batches by graded regeneration and differentiated sand adjustment of old sand in the production of large castings. To this end, we propose a graded regeneration and performance closed-loop sand adjustment process for old sand in large casting.
[0007] To achieve the above objectives, this application adopts the following technical solution: a graded regeneration and performance closed-loop sand adjustment process for large-scale foundry waste sand, comprising the following steps: S1: pre-treating the recycled waste sand after the large casting is unpacked to obtain waste sand to be regenerated; S2: dividing the waste sand to be regenerated into a first waste sand stream and a second waste sand stream; S3: performing a first regeneration treatment on the first waste sand stream to obtain first regenerated sand, and performing a second regeneration treatment on the second waste sand stream to obtain second regenerated sand, wherein the treatment intensity of the second regeneration treatment is higher than that of the first regeneration treatment; S4: adjusting the sand temperature of the first and second regenerated sand respectively, so that the first regenerated sand enters the first sand temperature window and the second regenerated sand enters the second sand temperature window, and the second sand temperature window is lower than the first sand temperature window; S5: temporarily storing the temperature-adjusted first and second regenerated sand respectively, and sending them to the sand mixing process together with new sand after metering; S6: adding binder and hardening material to the mixed sand formed by mixing the first regenerated sand, the second regenerated sand and new sand to obtain the finished mixed sand material.
[0008] Preferably, the pretreatment includes sequentially performing magnetic separation, crushing, fluidized bed cooling, and secondary magnetic separation on the recycled old sand.
[0009] Preferably, the first old sand stream and the second old sand stream are formed by splitting the stream through a distribution valve. Based on the total mass of the old sand to be regenerated, the mass ratio of the first old sand stream is 60%-85%, and the mass ratio of the second old sand stream is 15%-40%.
[0010] Preferably, the first regeneration process is a single-pass rubbing regeneration, and the processing time of the first old sand stream in the regeneration machine is 40s-90s.
[0011] Preferably, the second regeneration process is a rubbing regeneration process, and the processing time of the second old sand stream in the regeneration machine is 80s-150s.
[0012] Preferably, the first sand temperature window is 30℃-38℃, and the second sand temperature window is 24℃-34℃.
[0013] Preferably, the target temperature of the second sand temperature window is 3°C-8°C lower than the target temperature of the first sand temperature window.
[0014] Preferably, based on a total mass of 100 parts of sand entering the sand mixing process, the first recycled sand is 62-85 parts, the second recycled sand is 10-30 parts, and the new sand is 5-8 parts.
[0015] Preferably, the first recycled sand is 65-75 parts, the second recycled sand is 20-30 parts, and the new sand is 5-8 parts.
[0016] Preferably, the bonding material is furan resin, phenolic resin, or water glass, and the hardening material is an acidic curing agent or an organic ester curing agent used in conjunction with the bonding material.
[0017] The technical effects and advantages of this invention are as follows:
[0018] In this invention, the old sand to be recycled is divided into a first old sand stream and a second old sand stream, and then recycled at different intensities. This invention no longer treats the old sand as a single, uniform recycled sand stream, but rather allows the two types of recycled sand to form different recycling states before entering the mixing process. Subsequently, the sand temperature of the first and second recycled sands is adjusted so that the two types of recycled sand enter the subsequent sand blending and mixing process at different temperatures. Compared with the existing method of uniformly recycling and directly reusing old sand after uniform temperature adjustment, this invention controls the recycling intensity, sand temperature window, and sand blending ratio in the same process chain. This can reduce the differences between batches of mixed sand when a high proportion of old sand is recycled, and keep the usable time, tensile strength, and permeability within a relatively stable range, making it suitable for continuous recycling of old sand in the molding process of large castings. Attached Figure Description
[0019] The disclosure of this invention is illustrated with reference to the accompanying drawings. It should be understood that the drawings are for illustrative purposes only and are not intended to limit the scope of protection of this invention. In the drawings, the same reference numerals are used to refer to the same parts:
[0020] Figure 1 This is a schematic diagram of the waste sand grading, regeneration, and sand adjustment process of the present invention;
[0021] Figure 2 This is a batch-by-batch variation diagram of the usable time of the mixed sand under different process conditions of the present invention;
[0022] Figure 3 This is a comparison chart of batch fluctuation coefficients of mixed sand under different process conditions according to the present invention. Detailed Implementation
[0023] This embodiment provides a graded regeneration and performance closed-loop sand adjustment process for large-scale casting waste sand, which is suitable for the reuse of waste sand generated during the molding process of large castings.
[0024] It is especially suitable for resin self-hardening sand, water glass self-hardening sand, and other self-hardening sand systems formed by combining bonding and hardening materials.
[0025] Reference Figure 1 As shown, the process includes the following steps:
[0026] S1: Recycle the old sand after opening the box and then subject the old sand to magnetic separation, crushing, boiling cooling and secondary magnetic separation in sequence to obtain the old sand to be recycled;
[0027] Among them, magnetic separation is used to remove magnetic impurities such as iron pellets, cold iron fragments, and caster fragments from old sand; crushing is used to break up clumps in old sand, so that old sand can form a continuously transportable sand stream; boiling cooling is used to reduce the sand temperature after crushing and further loosen the old sand under agitation; and secondary magnetic separation is used to remove magnetic impurities that are still entrained after crushing and boiling cooling.
[0028] S2: Divide the old sand to be recycled into a first old sand flow and a second old sand flow;
[0029] The first old sand stream and the second old sand stream are separated by adjusting the opening ratio of the distribution valve. The first old sand stream enters the subsequent first regeneration process to form the first regenerated sand, and the second old sand stream enters the subsequent second regeneration process to form the second regenerated sand.
[0030] Based on the total mass of the old sand to be recycled, the mass ratio of the first old sand stream is 60%-85%, and the mass ratio of the second old sand stream is 15%-40%. The sum of the mass ratios of the first and second old sand streams is 100%. When the total reuse ratio of old sand increases, or when there is a large residual layer on the surface of the old sand to be recycled, the mass ratio of the second old sand stream can be increased accordingly.
[0031] S3: Perform the first regeneration treatment on the first old sand flow to obtain the first regenerated sand;
[0032] The first regeneration process includes passing the first old sand stream through the regenerator once and completing the rubbing regeneration inside the regenerator, wherein the time of the first regeneration process is 40s-90s, preferably 55s-70s;
[0033] When the first regeneration treatment time is less than 40 seconds, the loose residue on the surface of the first old sand flow is not removed sufficiently. If it is more than 90 seconds, the mechanical friction on the first old sand flow increases, which can easily cause sand particle wear and lead to an increase in fine powder content.
[0034] S4: Perform a second regeneration treatment on the second old sand flow to obtain the second regenerated sand;
[0035] The second regeneration process includes bringing the second old sand stream into a regeneration machine for rubbing and regeneration. The intensity of the second regeneration process is higher than that of the first regeneration process. After the process, the residual adhesive film, coating film or powder layer on the surface of the second old sand stream is weakened.
[0036] The regeneration time for the second regeneration process is 80s-150s, preferably 90s-120s. When the second regeneration process time is less than 80s, the weakening of the residual layer on the surface of the second old sand flow is insufficient; when it is more than 150s, it is easy to cause the fine powder content of the second regenerated sand to increase, which reduces the air permeability of the sand mold.
[0037] Optionally, the second regeneration process uses a two-pass regeneration machine for rubbing regeneration. When using a two-pass regeneration machine, the time for the second old sand stream to pass through the regeneration machine for the first time is 50s-80s, and the time for the second pass through the regeneration machine is 30s-60s.
[0038] S5: Adjust the sand temperature of the first recycled sand and the second recycled sand respectively, so that the first recycled sand enters the first sand temperature window and the second recycled sand enters the second sand temperature window, and the second sand temperature window is lower than the first sand temperature window;
[0039] The first sand temperature window is controlled at 30℃-38℃, preferably 32℃-36℃, and the second sand temperature window is controlled at 24℃-34℃, preferably 26℃-32℃. The target temperature of the second sand temperature window is 3℃-8℃ lower than the target temperature of the first sand temperature window.
[0040] After the sand temperature is adjusted, the first and second recycled sands are temporarily stored in the first and second old sand silos, respectively, for subsequent sand mixing.
[0041] Optionally, the first and second recycled sands can be regulated separately using different sand temperature regulating devices, or they can be regulated in batches using the same sand temperature regulating device.
[0042] S6: Take the first recycled sand, the second recycled sand and the new sand according to the preset ratio and send them into the sand mixing process;
[0043] Specifically, the first recycled sand is taken from the first old sand silo, and the second recycled sand is taken from the second old sand silo. After being weighed together with the new sand, they are sent to the sand mixer.
[0044] Among them, based on a total mass of 100 parts, the mass ratio of the first recycled sand, the second recycled sand and the new sand is controlled at 62-85:10-30:5-8, preferably 65-75:20-30:5-8;
[0045] When the mass percentage of the second recycled sand is less than 10%, the amount of the second recycled sand participating in the mixed sand is insufficient. When the mass percentage of the second recycled sand is greater than 30%, the usable time of the mixed sand is easily shortened.
[0046] S7: Add binder and hardener to the mixed sand formed by the first recycled sand, the second recycled sand and the new sand, and mix them to obtain the finished mixed sand material;
[0047] In one specific embodiment, the bonding material is furan resin or acid-cured phenolic resin, and the amount of bonding material added is 0.8%-1.6% of the mass of the mixed sand. The hardening material is an acidic curing agent, and the amount of hardening material added is 20%-60% of the mass of the bonding material. The acidic curing agent is selected from at least one of sulfonic acid curing agents and inorganic acid modified curing agents.
[0048] In one specific embodiment, the bonding material is an alkaline phenolic resin, and the amount of the bonding material added is 0.8%-1.6% of the mass of the mixed sand; the hardening material is an organic ester curing agent, and the amount of the hardening material added is 20%-60% of the mass of the bonding material.
[0049] In another specific embodiment, the bonding material is water glass, and the amount of the bonding material added is 2.0%-4.5% of the mass of the mixed sand. The hardening material is an organic ester hardener, and the amount of the hardening material added is 8%-25% of the mass of the water glass. The organic ester hardener is selected from at least one of glycerol triacetate, ethylene glycol diacetate, and diacetate hardeners.
[0050] The present invention will be further described below with reference to specific embodiments. It should be understood that the embodiments are only used to illustrate the specific implementation of the present invention and are not intended to limit the scope of protection of the present invention. Without departing from the concept of the present invention, those skilled in the art can make adaptive adjustments to each process parameter.
[0051] Example 1
[0052] This embodiment uses a furan resin self-hardening sand system, with furan resin as the bonding material and sulfonic acid curing agent as the hardening material. The amount of furan resin added is 1.2% of the mass of the mixed sand, and the amount of sulfonic acid curing agent added is 40% of the mass of the furan resin.
[0053] The old sand after the sand is unpacked is recycled. The old sand is then subjected to magnetic separation, crushing, boiling cooling and secondary magnetic separation in sequence to obtain old sand to be regenerated. By adjusting the opening ratio of the distribution valve, the old sand to be regenerated is divided into the first old sand stream and the second old sand stream. The mass ratio of the first old sand stream to the second old sand stream is 70:30.
[0054] The first old sand stream enters the regenerator for the first regeneration process, which takes 60 seconds, to obtain the first regenerated sand. The second old sand stream enters the regenerator for the second regeneration process, which takes 90 seconds, to obtain the second regenerated sand.
[0055] The first recycled sand was adjusted to 34℃±2℃, and the second recycled sand was adjusted to 28℃±2℃. The first and second recycled sands were temporarily stored after temperature adjustment.
[0056] When mixing sand, take 70 parts of first recycled sand, 25 parts of second recycled sand and 5 parts of new sand, and feed them into the sand mixer. Then add sulfonic acid curing agent and furan resin to mix and obtain the finished mixed sand.
[0057] Example 2
[0058] The bonding material, hardening material, and their addition amounts used in this embodiment are the same as in Example 1.
[0059] After the recycled old sand undergoes magnetic separation, crushing, fluidized bed cooling, and secondary magnetic separation, the old sand to be regenerated is obtained. By adjusting the opening ratio of the distribution valve, the old sand to be regenerated is divided into a first old sand stream and a second old sand stream, with a mass ratio of 80:20 between the first and second old sand streams.
[0060] The first old sand stream enters the regenerator for the first regeneration process, which takes 70 seconds, to obtain the first regenerated sand. The second old sand stream enters the regenerator for the second regeneration process, which takes 84 seconds, to obtain the second regenerated sand.
[0061] The first recycled sand was adjusted to 32℃±1℃, and the second recycled sand was adjusted to 29℃±1℃. The first and second recycled sands were temporarily stored after temperature adjustment.
[0062] When mixing sand, take 75 parts of first recycled sand, 20 parts of second recycled sand and 5 parts of new sand, and feed them into the sand mixer. Then add sulfonic acid curing agent and furan resin to mix and obtain the finished mixed sand.
[0063] Example 3
[0064] The bonding material, hardening material, and their addition amounts used in this embodiment are the same as in Example 1.
[0065] After the recycled old sand undergoes magnetic separation, crushing, fluidized bed cooling, and secondary magnetic separation, the old sand to be regenerated is obtained. By adjusting the opening ratio of the distribution valve, the old sand to be regenerated is divided into a first old sand stream and a second old sand stream, with a mass ratio of 60:40 between the first and second old sand streams.
[0066] The first old sand stream enters the regenerator for the first regeneration process, which takes 50 seconds, to obtain the first regenerated sand. The second old sand stream enters the regenerator for the second regeneration process, which takes 100 seconds, to obtain the second regenerated sand.
[0067] The first recycled sand was adjusted to 36℃±2℃, and the second recycled sand was adjusted to 28℃±2℃. The first and second recycled sands were temporarily stored after temperature adjustment.
[0068] When mixing sand, take 65 parts of first recycled sand, 30 parts of second recycled sand and 5 parts of new sand, and feed them into the sand mixer. Then add sulfonic acid curing agent and furan resin to mix and obtain the finished mixed sand.
[0069] Comparative Example 1
[0070] The pretreatment of old sand, bonding materials, hardening materials, and their amounts used in this comparative example are the same as in Example 1.
[0071] The old sand to be recycled is not separated into the first and second old sand flows, but is fed into the recycling machine as a whole for recycling treatment. The recycling time is 75 seconds, resulting in uniform recycled sand.
[0072] The temperature of the recycled sand was adjusted to 32℃±2℃. When mixing the sand, 95 parts of recycled sand and 5 parts of new sand were fed into the sand mixer. Then, sulfonic acid curing agent and furan resin were added and mixed to obtain mixed sand.
[0073] Comparative Example 2
[0074] The pretreatment of old sand, bonding materials, hardening materials, and their amounts used in this comparative example are the same as in Example 1.
[0075] By adjusting the opening ratio of the distribution valve, the old sand to be recycled is divided into a first old sand stream and a second old sand stream, with a mass ratio of 70:30 between the first and second old sand streams.
[0076] The first old sand stream enters the regenerator for the first regeneration process, which takes 60 seconds, to obtain the first regenerated sand. The second old sand stream enters the regenerator for the second regeneration process, which takes 90 seconds, to obtain the second regenerated sand.
[0077] The first and second recycled sands were both adjusted to 32℃±2℃. When mixing the sand, 70 parts of the first recycled sand, 25 parts of the second recycled sand and 5 parts of new sand were fed into the sand mixer. Then, sulfonic acid curing agent and furan resin were added and mixed to obtain mixed sand.
[0078] Comparative Example 3
[0079] The pretreatment of old sand, bonding materials, hardening materials, and their amounts used in this comparative example are the same as in Example 1.
[0080] The recycled sand is fed into the recycling machine for recycling. The recycling time is 75 seconds, resulting in uniform recycled sand. The uniform recycled sand is then divided into first temperature-adjusted sand and second temperature-adjusted sand. The first temperature-adjusted sand is adjusted to 34℃±2℃, and the second temperature-adjusted sand is adjusted to 28℃±2℃.
[0081] When mixing sand, take 70 parts of first temperature-adjusting sand, 25 parts of second temperature-adjusting sand and 5 parts of new sand and feed them into the sand mixer. Then add sulfonic acid curing agent and furan resin to mix and obtain mixed sand.
[0082] Comparative Example 4
[0083] The pretreatment of old sand, bonding materials, hardening materials, and their amounts used in this comparative example are the same as in Example 1.
[0084] By adjusting the opening ratio of the distribution valve, the old sand to be recycled is divided into a first old sand stream and a second old sand stream, with a mass ratio of 70:30 between the first and second old sand streams.
[0085] The first old sand stream enters the regenerator for the first regeneration process, which takes 60 seconds, to obtain the first regenerated sand. The second old sand stream enters the regenerator for the second regeneration process, which takes 90 seconds, to obtain the second regenerated sand.
[0086] The first recycled sand is adjusted to 28℃±2℃, and the second recycled sand is adjusted to 34℃±2℃. When mixing the sand, 70 parts of the first recycled sand, 25 parts of the second recycled sand and 5 parts of new sand are fed into the sand mixer. Then, sulfonic acid curing agent and furan resin are added and mixed to obtain mixed sand.
[0087] The mixed sand materials obtained in Examples 1-3 and Comparative Examples 1-4 were compared. All mixed sand materials were tested under the same environmental conditions. The ambient temperature was controlled at 25℃±2℃ and the relative humidity was controlled at 50%±10%. Five batches of mixed sand materials were prepared continuously for each group. The time of completion of mixing was recorded as the start time. The samples used for tensile strength and air permeability testing were prepared within 10 minutes after mixing.
[0088] In the usable time test, after each group of mixed sand was mixed, samples were taken every 5 minutes. When the sampling results showed that the mixed sand was close to losing its normal sample preparation state, the sampling interval was shortened to 1 minute, and the sample size was ≥1 kg each time. After sampling, the sand was filled, compacted, and demolded under the same conditions. If the mixed sand could be filled, compacted, and demolded normally, and the sand sample after demolding did not show obvious looseness, cracking, or corner collapse, then it was determined that the time point was still usable. If any of the following situations occurred: difficulty in filling, cracking after compaction, loosening after demolding, or corner collapse, the time of the last normal sample preparation was taken as the usable time of that batch of mixed sand. The results are shown in Table 1 below. Figure 2 As shown.
[0089] The 1-hour tensile strength was tested according to the test method for casting mixture strength in GB / T 2684-2025 "Test Methods for Foundry Sand and Mixtures". After the mixing of each group of mixed sands was completed, tensile strength test specimens for 1-hour tensile strength testing were prepared, with no less than 3 specimens per batch. The specimens were placed under the same environmental conditions for 1 hour after mixing was completed, and then the tensile strength was determined using a molding sand strength tester. If the test value of a single specimen deviated significantly due to sample preparation defects, loose sand inclusions, or abnormal fracture position, the data was not included in the test results of that batch, and a new specimen was prepared under the same conditions. The results are shown in Table 1 below.
[0090] The sample preparation method for 24-hour tensile strength is the same as that for 1-hour tensile strength. After the mixed sand is mixed, tensile strength samples for 24-hour tensile strength testing are prepared separately for each batch, with no less than 3 samples per batch. After the samples are placed under the same environmental conditions for 24 hours, the tensile strength is measured using the same type of sand strength testing machine. The 1-hour tensile strength is used to evaluate the early hardening of the mixed sand, and the 24-hour tensile strength is used to evaluate the strength level of the mixed sand after hardening. The results are shown in Table 1 below.
[0091] The air permeability was tested according to the air permeability test method in GB / T 2684-2025 "Test Methods for Sand and Mixtures for Foundry". After the mixed sand materials of each group were mixed, air permeability test samples were prepared. After the test samples were placed at room temperature until they could be stably transported, they were tested using a molding sand air permeability tester. At least 3 test samples were tested in the same batch. If a test sample had obvious cracks, missing corners or uneven compaction, the test sample was not included in the test results and was retested under the same conditions. The results are shown in Table 1 below.
[0092] Table 1. Batch-by-batch test results of mixed sand under different process conditions
[0093]
[0094] Based on the test results of five consecutive batches in Table 1, the average value and standard deviation of each test index were calculated using SPSS 26.0, and the results are shown in Table 2 below.
[0095] Table 2. Mean and standard deviation of test results
[0096]
[0097] To further compare the batch variation of different testing indicators, the coefficient of variation was calculated based on the mean and standard deviation in Table 2. The coefficient of variation is the ratio of the standard deviation to the mean. The calculation results are shown in [Table 2]. Figure 3 As shown.
[0098] From Table 1 and Table 2, Figure 2 and Figure 3 It can be seen that the indicators of Examples 1-3 did not simply increase synchronously, but showed changes corresponding to the direction of process adjustment. The usable time, 1-hour tensile strength, 24-hour tensile strength and air permeability of Example 1 were relatively balanced. The usable time and air permeability of Example 2 were relatively high, but the early tensile strength was slightly low. The 1-hour tensile strength of Example 3 was relatively high, but the usable time was shortened and the air permeability was slightly reduced.
[0099] Looking at the batch fluctuations, the standard deviation of usable time for Examples 1-3 is 1.14 min-1.30 min, the standard deviation of tensile strength at 1 hour is 0.01 MPa-0.02 MPa, the standard deviation of tensile strength at 24 hours is about 0.02 MPa, and the standard deviation of permeability is 1.92-2.39. In contrast, the fluctuations of the corresponding indicators in Comparative Examples 1-4 are significantly amplified, especially the usable time and permeability. For the molding of large castings, such fluctuations will directly affect the consistency of sand filling, compaction, mold repair, and sand mold venting.
[0100] The above results show that by adjusting the temperature of the two types of recycled sand separately before mixing them with new sand, the present invention can reduce the differences between batches of mixed sand when a high proportion of old sand is reused, so that the usable time, tensile strength and air permeability are kept within a relatively stable range.
[0101] The technical scope of this invention is not limited to the content described above. Those skilled in the art can make various modifications and variations to the above embodiments without departing from the technical concept of this invention, and all such modifications and variations should fall within the protection scope of this invention.
Claims
1. A large-scale casting waste sand graded regeneration and performance closed-loop sand adjustment process, characterized in that, Includes the following steps: S1: Pre-treat the recycled old sand after large castings are unpacked and removed from the box to obtain old sand to be recycled. S2: Divide the old sand to be recycled into a first old sand stream and a second old sand stream; S3: Perform a first regeneration treatment on the first old sand flow to obtain first regenerated sand, and perform a second regeneration treatment on the second old sand flow to obtain second regenerated sand. The treatment intensity of the second regeneration treatment is higher than that of the first regeneration treatment. S4: Adjust the sand temperature of the first recycled sand and the second recycled sand respectively, so that the first recycled sand enters the first sand temperature window and the second recycled sand enters the second sand temperature window, and the second sand temperature window is lower than the first sand temperature window; S5: Temporarily store the temperature-adjusted first and second recycled sands separately, and then send them together with the new sand into the sand mixing process after being measured. S6: Add binder and hardener to the mixed sand formed by mixing the first recycled sand, the second recycled sand and the new sand to obtain the finished mixed sand material.
2. The large-scale foundry waste sand classification, regeneration, and performance closed-loop sand adjustment process according to claim 1, characterized in that: The pretreatment includes sequentially performing magnetic separation, crushing, fluidized bed cooling, and secondary magnetic separation on the recycled old sand.
3. The large-scale foundry waste sand classification, regeneration, and performance closed-loop sand adjustment process according to claim 1, characterized in that: The first old sand stream and the second old sand stream are formed by splitting the flow through a distribution valve. Based on the total mass of the old sand to be regenerated, the mass ratio of the first old sand stream is 60%-85%, and the mass ratio of the second old sand stream is 15%-40%.
4. The large-scale foundry waste sand graded regeneration and performance closed-loop sand adjustment process according to claim 1, characterized in that: The first regeneration process is a single-cycle rubbing regeneration, and the processing time of the first old sand stream in the regeneration machine is 40s-90s.
5. The large-scale foundry waste sand classification, regeneration, and performance closed-loop sand adjustment process according to claim 1, characterized in that: The second regeneration process is a rubbing regeneration, and the processing time of the second old sand stream in the regeneration machine is 80s-150s.
6. The large-scale foundry waste sand classification, regeneration, and performance closed-loop sand adjustment process according to claim 1, characterized in that: The first sand temperature window is 30℃-38℃, and the second sand temperature window is 24℃-34℃.
7. The large-scale foundry waste sand classification, regeneration, and performance closed-loop sand adjustment process according to claim 1, characterized in that: The target temperature of the second sand temperature window is 3℃-8℃ lower than the target temperature of the first sand temperature window.
8. The large-scale foundry waste sand graded regeneration and performance closed-loop sand adjustment process according to claim 1, characterized in that: Based on a total mass of 100 parts of sand entering the sand mixing process, the first recycled sand is 62-85 parts, the second recycled sand is 10-30 parts, and the new sand is 5-8 parts.
9. The large-scale foundry waste sand classification, regeneration, and performance closed-loop sand adjustment process according to claim 8, characterized in that: The first recycled sand consists of 65-75 parts, the second recycled sand consists of 20-30 parts, and the new sand consists of 5-8 parts.
10. The large-scale foundry waste sand classification, regeneration, and performance closed-loop sand adjustment process according to claim 1, characterized in that: The bonding material is furan resin, phenolic resin or water glass, and the hardening material is an acidic curing agent or an organic ester curing agent used in conjunction with the bonding material.
Citation Information
Patent Citations
Casting curing agent content auxiliary control apparatus
CN102847879A
Method for treating and casting reclaimed sand through water mists
CN107983909A
Resin sand regenerating system
CN206936276U
